Occupational health and safety - Burke, Ronald J.; Clarke, Sharon , 1968-; Cooper, Cary L. (Psychological and behavioral aspects of risk series, 2011)
The International Labour Organization (ILO) estimates that every year there are 2.2 million fatal and 270 million non-fatal accidents or occupational diseases worldwide. Occupational Health and Safety looks at the research into what causes accidents and errors in the workplace. Emphasizing the psychological and behavioural aspects of risk in organizations, it includes case studies and best practices. The contributors to this volume come from various countries, reflecting unique interest and knowledge in particular areas